2008
DOI: 10.1007/s00128-008-9600-9
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers in Mudsnails (Cipangopaludina cahayensis) and Sediments from an Electronic Waste Recycling Region in South China

Abstract: Mudsnails and sediments from an electronic waste recycling region in South China were chosen to study the polybrominated diphenyl ethers (PBDEs) bioavailability of mudsnail in different ambient levels. Significant (p \ 0.05) correlations of biota-sediment accumulation factor (BSAF) versus the reciprocal of PBDE concentration in sediment (1/Sed) occurred in all quantitative PBDE congeners except BDE-209, showed that the BSAFs of PBDEs in mudsnails were increased with reciprocal increasing ambient levels. The BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
5
13
2
Order By: Relevance
“…These values were consistent with those (0.0002-0.002) determined in mudsnails from another e-waste recycling site in South China (Yang et al, 2009). However, the calculated BSAFs for BDE 209 in the present study are generally 1-2 orders magnitude lower than our earlier reported values (averages of 0.02-0.11) in several marine fish and shrimp species collected from the Pearl River Estuary, South China (Xiang et al, 2007).…”
Section: Comparison With Extremely Hydrophobic Pcbs and Bde 209supporting
confidence: 90%
“…These values were consistent with those (0.0002-0.002) determined in mudsnails from another e-waste recycling site in South China (Yang et al, 2009). However, the calculated BSAFs for BDE 209 in the present study are generally 1-2 orders magnitude lower than our earlier reported values (averages of 0.02-0.11) in several marine fish and shrimp species collected from the Pearl River Estuary, South China (Xiang et al, 2007).…”
Section: Comparison With Extremely Hydrophobic Pcbs and Bde 209supporting
confidence: 90%
“…Polybrominated diphenyl ethers with the largest BSAFs 28 (BDEs 28/33, 66) had log K OW of approximately 6 to 7, with lower accumulation of the more hydrophobic congeners. This trend was generally consistent with other studies investigating BDE uptake by deposit feeders [27,28], other studies of HOC uptake by deposit feeders [36], and highly chlorinated PCBs specifically [37]. For HOCs with log K OW greater than 7, bioavailability generally decreases with increasing molecular weight because of stronger associations with sediment particles and lower solubility in water and digestive fluids.…”
Section: Bsafssupporting
confidence: 86%
“…Similar to what was observed in the spiked sediment exposures, BSAFs 28 generally decreased with increasing K OW , with the penta-BDE congener BSAFs 28 two orders of magnitude higher than the BSAF 28 for congeners in the deca-BDE mixture (Fig. 5).…”
Section: Bsafssupporting
confidence: 85%
See 2 more Smart Citations